2015
DOI: 10.1016/j.firesaf.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of the flame inhibition efficiency of transition metals using metallocenes

Abstract: a b s t r a c tThis study aimed to directly and systematically compare the flame inhibition abilities of various transition metals, including vanadium, ruthenium, osmium, chromium, manganese, iron, cobalt, and nickel, by using the corresponding metallocenes: vanadocene, ruthenocene, osmocene, chromocene, manganocene, ferrocene, cobaltocene, and nickelocene. The downward flame spread rates over filter paper samples on which each metallocene was adsorbed were measured. In addition, thermogravimetric measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Of the transition metal compounds, commercially available ferrocene (FeCp2) shown in Fig. 1a is expected to become a new flame inhibitor, based on recent studies (Koshiba et al, 2015a). Linteris et al (2000) first reported that 200-ppm ferrocene vapor significantly reduces the burning velocity of premixed methane/air flames.…”
Section: Introductionmentioning
confidence: 99%
“…Of the transition metal compounds, commercially available ferrocene (FeCp2) shown in Fig. 1a is expected to become a new flame inhibitor, based on recent studies (Koshiba et al, 2015a). Linteris et al (2000) first reported that 200-ppm ferrocene vapor significantly reduces the burning velocity of premixed methane/air flames.…”
Section: Introductionmentioning
confidence: 99%
“…As will be noted later, all four variables were kept constant. Hence, the filterpaper combustion experiments allowed us to directly chemically compare the flame inhibition efficiency among the calcium compounds [22].…”
Section: Downward Flame-spread Rates Over Solid Fuelsmentioning
confidence: 99%
“…Since iron ions have various oxidation states and can form hydroxides/oxides with water/oxygen in the air during combustion. The resulting iron‐bearing intermediates can eliminate the free radicals produced in the combustion process to terminate the chain reaction 28 . On the other hand, in the early stage of smoke production, some iron oxides deposit on the surface of substrates to form condensation nuclei, reducing the smoke generation rate.…”
Section: Introductionmentioning
confidence: 99%